Relationship between landscape and river ecosystem services - M. Dede; S. Sunardi; K.C. Lam; S. Withaningsih (Global Journal of Environmental Science and Management)
Landscape dynamics are a consequence of population growth, which can degrade river ecosystem services. Since various countries approved the millennium ecosystem assessment, it has inspired researchers to examine the relationship between landscape and river ecosystem services. Therefore, this study aims to summarize previous studies about landscape and river ecosystem services using a systematic literature review. This study referred to the preferred reporting items for systematic reviews and meta-analysis. Data were obtained from six databases of scientific publications such as Scopus, Pubmed, Directory of Open Access Journals, Scilit, Neliti, and Garba Rujukan Digital. The results show that research on this topic has spread worldwide. Landscape data, reflected in land use and land cover, came from various sources containing geospatial information and is combined with field surveys. There were 3-18 types of land use and land cover and it did not always reflect detailed information about the research area. Meanwhile, nutrient regulation and water quality attracted the most attention for river ecosystem services. The interaction between the two variables is revealed through inferential statistics and modeling. As representations of the natural landscape, forests and grasslands have a positive and significant contribution to river ecosystem services. Therefore, knowledge of landscape and river ecosystem services is a preliminary effort to understand environmental processes in achieving sustainability, also valuable input for conservation and rehabilitation strategies in many countries. This review can be a proper reference for environmental management, especially in the landscape changes related to river ecosystem services.